Mammal species richness and new records in protected natural areas of the northern part of the metropolitan area of the Valley of México - Hortelano-Moncada, Yolanda; Barragán-Saldaña, Asela Samari; Fernández-Reyes, Jesús R.; Cervantes, Fernando A.; Barragán Guerrero, Leonardo; Gómez-Naranjo, M. Vianey (THERYA, 2021)
Sierra de Guadalupe is the only mountain range in the northern part of the Valley of Mexico metropolitan area. The accelerated urban expansion over the past decades has turned Sierra de Guadalupe into an isolated natural area immersed within the urban matrix. This study aimed to gather a documented inventory of the mammals of Sierra de Guadalupe as such information is useful to improve the management, restoration, and conservation of this important natural area of the basin of Mexico. Mammal collection records were extensively surveyed in the literature, collection databases, web pages, and scientific collections; field surveys were also conducted. A taxonomic list of the mammal species and their conservation status in the four Protected Natural Areas of Sierra de Guadalupe was compiled. A species-accumulation curve was constructed using the Chao 1 model and a map showing the distribution of collection records was produced. This work reveals that the mammals of Sierra de Guadalupe include 29 species, 23 genera, 15 families, and six orders. Six species are endemic to Mexico; two of them, Choeronycteris mexicana and Cratogeomys fumosus, are listed as threatened and one, Leptonycteris yerbabuenae, as under special protection. Collection records were gathered from 62 different localities. The largest number of species records and collections were made between 2009 and 2020. The species-accumulation curve projects a total of 36 mammal species. This is the first documented inventory ever compiled of the wild mammals of Sierra de Guadalupe. The species richness observed in this area is remarkable, considering its extension and environmental stressors; in addition, it harbors species endemic to Mexico, some of which are threatened. This is the first time that the species Sorex saussurei, Choeronycteris mexicana, Leptonycteris yerbabuenae, Cratogeomys merriami, Neotomodon alstoni, and Peromyscus melanophryshave been recorded in this area. The species-accumulation curve indicates that our inventory provides a good representation of the local species assemblage. This information can support the formulation of action plans for the conservation and restoration of the biological diversity of these important Protected Natural Areas and the last significant natural area remaining in the northern part of the Valley of Mexico Metropolitan Area.